Study on the Size and Occurrence Effects of Equivalent Elasticity Modulus of Orthogonal Random Jointed Rock Masses - Naizhong, Xu; Changqing, Liu; Chang, Su; Tian, Zhou (Frontiers in Earth Science, 2022)
Under the engineering background of a +144m mining platform on an open pit slope of Xinqiao Mining Corporation, the eigenvalue distribution function of joints was acquired based on the massive statistics of field joints. Next, an orthogonal random joint model was constructed using Monte-Carlo method based on UDEC software platform. Subsequently, the Representative Elementary Volume (REV) size and occurrence effects of the equivalent elasticity modulus of the orthogonal random jointed rock mass were explored through numerical experiments with lots of discrete elements. The results showed that the equivalent elasticity modulus of the orthogonal random jointed rock mass was of evident size effect, and the relationship between the mean equivalent elasticity modulus Eeq and the REV size of the rock mass followed the negative power function distribution. Before the model size reached the REV size, its Eeq was greatly discrete. Under different joint angles, both the standard deviation σf and coefficient of variation δ of the equivalent elasticity modulus of this model presented discrete distribution. As the model size reached the REV size, the mean equivalent elasticity modulus Eeq showed the “two-high and one-low” morphological distribution. Eeq was small when the main joint angle was α∈[30°，40°], but it was large when α=0° or 90°. δ was taken as 10%, so the REV size of the corresponding Eeq was 10 m×20 m. When the model size reaches the REV size, the occurrence effect of its equivalent elasticity modulus was no longer significant.